Treatment and outcome of out-of-hospital cardiac arrest in outpatient health care facilities. (December 2015) - Kudenchuk, Peter J.; Stuart, Russell; Husain, Sofia; Fahrenbruch, Carol; Eisenberg, Mickey
Abstract: Aim: We evaluated the frequency and effectiveness of basic and advanced life support (ALS) interventions by medical professionals when out-of-hospital cardiac arrest (OHCA) occurred in ambulatory healthcare clinics before emergency medical services (EMS) arrival. Methods: Non-traumatic OHCAs in adults were systematically characterized over a 15 year period by their occurrence in clinics, at home, or in non-medical public locations, and outcomes compared between matched cohorts from each group. Results: Among 7784 patients, 6098 OHCA occurred at home, 1612 in non-medical public locations and 74 in clinics. Compared to non-medical public locations, clinic patients with OHCA were older, more often women and more frequently shocked; clinic arrests were more often witnessed, less likely to be of cardiac cause and to occur before EMS arrival. Compared to home, more clinic arrests were witnessed, occurred after EMS arrival, had bystander CPR, shockable rhythms and were defibrillated. When OHCA occurred before EMS arrival, 51 of 56 clinic patients (91%) received CPR, a defibrillator applied to 23 (41%), 17 (30%) were shocked, 4 (7%) intubated, and 7 (13%) received intravenous medications from facility personnel. Of these, only pre-EMS defibrillator use was associated with improved outcome. Among matched patients, OHCA survival was higher in clinics than at home (42% vs 26%, p = 0.029), but comparable to other public locations. Conclusions: Survival from OHCA in clinics was comparable to non-medical public locations, and higher than at home. Alongside CPR, use of defibrillators was associated with improved survival and worth prioritizing over other interventions before EMS arrival regardless of OHCA location.